2014
DOI: 10.1016/j.jelekin.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of telemetric electromyography and near-infrared spectroscopy during high-intensity resistance exercise

Abstract: However, it is likely that biological variation during multi-joint isotonic resistance exercise may account for some of the variation in the observed results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…Research which has observed significantly lower levels of muscular oxygenation in hypoxia has employed long exposures to moderate terrestrial altitude (3 h at 1800 m) during resistance exercise (Oguri et al ., ) or a more severe level of hypoxia (F I O 2 = 10–12%) at rest (Richardson et al ., ; Rupp et al ., ). Furthermore, biological variations in the muscular oxygen flux can influence the reliability of NIRS variables during high‐load dynamic resistance exercise (Scott et al ., ). Based on these findings, it would appear that IHRT using high‐load resistance exercise is not likely to provide a sufficient stress to alter muscle oxygenation; however, further research is required to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research which has observed significantly lower levels of muscular oxygenation in hypoxia has employed long exposures to moderate terrestrial altitude (3 h at 1800 m) during resistance exercise (Oguri et al ., ) or a more severe level of hypoxia (F I O 2 = 10–12%) at rest (Richardson et al ., ; Rupp et al ., ). Furthermore, biological variations in the muscular oxygen flux can influence the reliability of NIRS variables during high‐load dynamic resistance exercise (Scott et al ., ). Based on these findings, it would appear that IHRT using high‐load resistance exercise is not likely to provide a sufficient stress to alter muscle oxygenation; however, further research is required to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…After back squat After deadlift the reliability of NIRS variables during high-load dynamic resistance exercise (Scott et al, 2014b). Based on these findings, it would appear that IHRT using high-load resistance exercise is not likely to provide a sufficient stress to alter muscle oxygenation; however, further research is required to confirm these findings.…”
Section: Preexercisementioning
confidence: 94%
“…28 The coefficient of variation (CV) was calculated as a characteristic of the performance of within-subject evaluation, 29 with a CV below 5% to 10% considered as acceptable absolute reliability. 26 All statistical analyses were performed using Microsoft Excel and GraphPad Prism 7.…”
Section: Test-retest Reliability and Sensitivity Of Devices At Restmentioning
confidence: 99%
“…10,24 The PortaMon, a widely used, portable, SRS oximeter has previously demonstrated a high level of reliability at rest 25 and during isotonic, multijoint resistance exercise. 26 Conversely, no studies investigating the test-retest reliability of the MOXY device have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…1 Multimodal studies of muscle function are becoming increasingly common, most of them based on a combination of NIRS and EMG. 18,22,23 Many of these studies focus on investigating the relationship between muscle electrophysiology and oxygenation or hemodynamics [24][25][26][27][28] or on gathering more reliable information on, for example, neuromuscular and metabolic activity in relation to muscle fatigue or injury. 29,30 Moreover, wireless hybrid sEMG/NIRS sensors have recently been proposed for multimodal analysis by such researchers as Guo et al 34 Surface EMG and accelerometer (ACM) have been previously used for example for sign language recognition, 45 fatigue assessment, 46 Parkinson's disease progress assessment 47 and for monitoring daily activities of patients who have had a stroke.…”
mentioning
confidence: 99%